William Lane Craig’s “Biblical” Doctrine of the Trinity - Gaston, Thomas E. (Heythrop journal, 2025)
This article critically examines William Lane Craig’s defence of what he terms the ‘biblical doctrine of the Trinity’ as presented in his contribution to One God, Three Persons, Four Views and his Systematic Philosophical Theology. Craig formulates this doctrine using two core propositions: (1) there is exactly one God; and (2) there are exactly three distinct persons properly called ‘God’. While Craig contends that his formulation represents a biblical justification for the Trinity, the paper argues that his case is ultimately unconvincing. This article examines aspects of Craig’s argument, including his remarkable claim that the New Testament authors lacked the concept of the identity relation. I argue that whilst the New Testament authors affirmed one God, they did so in a sense different from that required for Craig’s ‘biblical’ doctrine of the Trinity. His second proposition is equivocal and his criteria for evaluation are not specified. The milieu and the pattern of usage within the New Testament mean that finding a maximum of eight texts to justify his second proposition is surprising and tells against his conclusions. Therefore, the prior probability weighs strongly in favour of the alternative explanations for these eight texts that scholars have proposed.